2009
DOI: 10.3941/jrcr.v3i3.108
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty and spinal cord compression: a case report

Abstract: This report describes a 60-year-old woman with intensive back pain due to metastatic vertebral body collapse, who underwent percutaneous vertebroplasty. Subsequently, the patient developed metastatic lesion extrusion into the spinal canal because of pressure of the cement, with compression of the left anterolateral spinal cord. During percutaneous vertebroplasty procedure in patient with malignant tumors, the complication rate increases owing to the risk of leakage of cement resulting from the vertebral body d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on a meta-analysis, the clinical efficacy showed that OVCFs patients who underwent VAP treatment were 22% less likely to die at up to 10 years than those receiving nonsurgical treatment [106]. However, the prevalence of severe complications related to VAP could be as high as 12.5-36.8% [108][109][110][111][112]. The most common complications encountered are cement leakage and new OVCFs at the adjacent level.…”
Section: Surgery Treatmentmentioning
confidence: 99%
“…Based on a meta-analysis, the clinical efficacy showed that OVCFs patients who underwent VAP treatment were 22% less likely to die at up to 10 years than those receiving nonsurgical treatment [106]. However, the prevalence of severe complications related to VAP could be as high as 12.5-36.8% [108][109][110][111][112]. The most common complications encountered are cement leakage and new OVCFs at the adjacent level.…”
Section: Surgery Treatmentmentioning
confidence: 99%
“…Another challenge is that VAP is not suitable for patients with surgical contraindications 19 . In addition, the prevalence of severe complications related to VAP could be as high as 12.5%–36.8% 20 , 21 , 22 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%